2019
DOI: 10.33785/ijds.2019.v72i02.015
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of dairy based farmer producer companies in Kerala

Abstract: A study on the genesis of dairy based farmer producer companies was carried out in five companies of Kerala. From each company 24 members were randomly selected. Reasons behind the formation of company were analyzed statistically. The study revealed that 96.66 percent of respondents viewed better price realization through direct sale of farm produce by eliminating middleman as the foremost reason of company formation followed by availability of farm inputs at reasonable rate (90.83%) and benefits from various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It concludes that FPOs were highly effective in improving the members' human, social and political dimensions of livelihood. Jose et al [23] studied why farmer groups formed FPCs through five dairy-based FPCs in Kerala. Direct sales and the availability of farm inputs turned out to be the main reasons small and marginal farmers formed FPCs.…”
Section: Studies On Fpos In Indiamentioning
confidence: 99%
“…It concludes that FPOs were highly effective in improving the members' human, social and political dimensions of livelihood. Jose et al [23] studied why farmer groups formed FPCs through five dairy-based FPCs in Kerala. Direct sales and the availability of farm inputs turned out to be the main reasons small and marginal farmers formed FPCs.…”
Section: Studies On Fpos In Indiamentioning
confidence: 99%
“…These producer organizations were also engaged in community mobilization through the self-help groups. In Kerala, the milk producers were found to be attached with the producer company due to better price realization, availability of inputs at a reasonable rate and receiving benefits from the government schemes (Jose et al, 2019). A study by Mukherjee et al (2020) in the Bundelkhand region of Madhya Pradesh, India, observed that joining farmers’ producer companies helped the milk producers to enhance their annual income from milk, higher social participation with progressive dairy farmers, extension agencies and urban contacts significantly.…”
Section: Review Of Literaturementioning
confidence: 99%
“…These organisations combine the business principles of company and welfare aspects of co-operatives. There are evidence of better price realisation when farmers join together to form dairy based producer organisations (Jose et al 2019a). Producer organization is a generic name that represents various cooperatives, self help groups, federation of SHGs, commodity interest groups, farmers club, producer company etc.…”
Section: Introductionmentioning
confidence: 99%